S-RNase is secreted from transmitting tract cells into the intercellular spaces after pollen tubes enter the style in apple (Malus pumila Mill.) - Li, Tian-Zhong; Katoh, Naoki; Miyairi, Kazuo; Okuno, Toshikatsu (The journal of horticultural science & biotechnology, 2007)
Apple shows gametophytic self-incompatibility (GSI). The phenomenon of GSI in pistils is controlled by S-RNases expressed specifically in the style. The localisation and redistribution of S-RNases in the styles of the apple cultivar 'Starking Delicious', before and after pollination, were investigated using immunocytochemical electron microscopy and immunohistochemical light microscopy. In the case of non-pollination, S-RNases were synthesised and remained in the transmitting tract cells. Conversely, 24 h after either self- or cross-pollination, S-RNases were found to be concentrated in the intercellular space and distributed evenly in the cytoplasm of pollen tubes in vivo and in vitro. Moreover, two kinds of transmitting tract cells, those producing and not producing S-RNase, were observed in the styles of apple.